Low-cost, Arduino-based, portable device for measurement of methane composition in biogas. (August 2019) - Yang, Shunchang; Liu, Yikan; Wu, Na; Zhang, Yingxiu; Svoronos, Spyros; Pullammanappallil, Pratap
Abstract: An inexpensive, portable device to measure methane content of biogas samples was constructed. The central component of the device was an MQ-4 methane sensor. This sensor, along with humidity, temperature and pressure sensors, was enclosed in an airtight glass jar and interfaced with a programmable Arduino Uno clone for data logging and operation. The sensor was able to detect methane within the jar to as low as 400 ppm, but responded linearly to concentrations ranging from about 4000 to 110, 000 ppm. Measurements made by the sensor were compared to analysis by a gas chromatograph equipped with a thermal conductivity detector. Analysis of biogas samples from an anaerobic digester using the device produced an average absolute error of 0.69 ± 0.55% when compared to GC measurements. Using 10 ml biogas sample size, methane content as low as 18% by volume could be reliably measured by the device. By increasing sample to 90 ml, methane content as low as 2.4% could be analyzed. This device was assembled for a cost of US$37. A field version that includes an LED display and power pack could be assembled for under US$50. Highlights: Low cost low range MQ-4 sensor was used to measure methane content of biogas. A device which incorporated the sensor was assembled for a cost of US$37. Device for field applications can be assembled for about US$47. The device could measure methane content as low as 2.4% in biogas samples. Measure actual biogas sample methane to an average absolute error of 0.69 ± 0.55%.